2021
DOI: 10.17275/per.21.96.8.4
|View full text |Cite
|
Sign up to set email alerts
|

Values Education Practices in Preschool: The Case of Turkey and the United States

Abstract: In this study, the aim is to determine national and universal values that are tried to be taught to children in pre-school education institutions of different cultures and to compare programs and practices in the context of value education within the framework of teachers' views. Case study, one of the qualitative research methods, was used in the study. In the study, criterion and convenience sampling methods, one of the purposive sampling methods, were used in determining the study group. In this context, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…To comprehend how an event occurred, i.e., what is occurring in the background, it is necessary to identify and comprehend the values that guide the attitudes and behaviors of the individuals responsible for the event (Sahin, 2019). Through effective value education, cognitive, affective, and behavioral differences of individuals develop (Caliskan, Yildirim, & Demirhan, 2021) When the literature on values is examined, most of the studies were conducted with pre-service teachers (Arslan, 2022;Yenen & Ulucan, 2021;Akıturk & Kahraman, 2019;Akhan, Subası, & Acıl, 2020). Kinacı (2018) revealed that pre-service social studies teachers prioritized values such as patriotism, respect, love, justice, equality, responsibility, and independence more than other values.…”
Section: Introductionmentioning
confidence: 99%
“…To comprehend how an event occurred, i.e., what is occurring in the background, it is necessary to identify and comprehend the values that guide the attitudes and behaviors of the individuals responsible for the event (Sahin, 2019). Through effective value education, cognitive, affective, and behavioral differences of individuals develop (Caliskan, Yildirim, & Demirhan, 2021) When the literature on values is examined, most of the studies were conducted with pre-service teachers (Arslan, 2022;Yenen & Ulucan, 2021;Akıturk & Kahraman, 2019;Akhan, Subası, & Acıl, 2020). Kinacı (2018) revealed that pre-service social studies teachers prioritized values such as patriotism, respect, love, justice, equality, responsibility, and independence more than other values.…”
Section: Introductionmentioning
confidence: 99%